Synthesization And Characterization Of Graphitic Carbon Nitride (g-C3N4) And Coconut Shell Husk Derived-Carbon Composite - Nurul Sakinah, Zakariah (2023)
One of the main environmental issues is industrial wastewater discharge. Water contamination by dye discharges from various industries such as paper making, textile dyeing, cosmetics, paints and food processing can affect human health if discharged into water because they are toxic, carcinogenic, and xenobiotic. Conventional photocatalyst like titanium dioxide (TiO2) is commonly used in Malaysia to treat dye wastewater. However, this semiconductor has their own drawbacks because of the huge band gap energy, which results in poor performances. The aims of this research are to create a synthesization graphitic carbon nitride (g-C3N4) and coconut shell husk derived carbon composite, and characterize its properties and activity as a catalyst. In this study, photocatalytic semiconductors will be prepared in the form of powders by synthetic methods like the hydrothermal method. Pure carbon and pure graphitic carbon nitride (g-C3N4) will characterize by using x-ray diffractometer (XRD) and scanning electron microscope-energy dispersive x-ray (SEM-EDX), fourier-transform infrared (FTIR), and ultraviolet visible spectroscope (UV-Vis) analyzer. Characterization is important step in studying the structure of the catalyst surface, composition of the catalyst, and the chemical properties of the catalyst. g-C3N4 is successfully fabricated due to the narrow band gap and discovered metal-free sonocatalyst. As a result, g-C3N4 can be used in the dye wastewater treatment. Apart from this, it can meet Sustainable Development Goals (SDG) 6 (clean water and sanitation) because dye wastewater can be treated and dangerous contaminants such as toxics, carcinogens, and xenobiotics can be reduced. In short, it can help to reduce environmental problems while also protecting human health.